PERSEPSI PASIEN PENYAKIT GINJAL KRONIK YANG MENJALANI HEMODIALISIS TERHADAP PERMASALAHAN DISFUNGSI EREKSI - Wahyuningtyas, Eka Sakti; Chasani, Shofa; Hidayati, Wahyu (Journal Of Holistic Nursing Science, 2016)
Chronic Kidney Disease is a disorder of renal function are progressive and irreversible. Male patients with Chronic Kidney Disease undergoing hemodialysis may have an experience with sexual dysfunction problems is erectile dysfunction. The problem of erectile dysfunction can be a complex psychosocial problems such as depression. Perceptions and expectations of patients with chronic kidney disease who undergoing hemodialysis with erectile dysfunction to sexual fulfillment nursing care needs to be known and have not been studied until now. The research had toexplore the experiences of patients with chronic kidney disease who undergoing hemodialysis with erectile dysfunction. Methods of the research is a qualitative research design with a phenomenological approach. Subjects were patients with chronic kidney disease who undergoing hemodialysis with erectile dysfunction in Hemodialysis Unit RS Tk II.04.05.01 Dr.Soedjono Magelang many as seven people The collection of data by means of indepth interviews. The study was conducted in February-April 2016. In this research have the three themes, the perception initial of the chronic kidney disease and erectile dysfunction, the factors that cause erectile dysfunction, attitudes and feelings the patients related to the condition of erectile dysfunction.Patients with chronic kidney disease who undergoing hemodialysis with erectile dysfunction have a perception that the condition of the disease and hemodialysis therapy effect on erectile dysfunction problems.